The Effect of Motivation on Employee Performance with Work Discipline as Mediating Variable at Pos Indonesia Bekasi Main Branch - Dewi, Syntia; Widigdo, Aslam Mei Nur (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2024)
The purpose of this research is to quantify and examine the impact of employee motivation on performance, with work ethics serving as a mediating factor. The population in this research amounted to 260 employees of PT Pos Indonesia Bekasi Main Branch. The sample used in the research amounted to 50 employees, calculated based on the Slovin formula. The technique used is probalility sampling and the sample method used is simple random sampling. The data collection method uses a survey method with data collection in the form of a questionnaire. Furthermore, the data is processed through SmartPLS version 3 and the Data Analysis Method with PLS-SEM. The results of this research concluded that Motivation has a positive and significant influence on Work Discipline; Work Discipline has a positive and significant influence on Employee Performance and Motivation has a positive and significant influence on Employee Performance. Then Motivation has a positive and significant influence on Employee Performance through mediation of Work Discipline.